CEU Graduation Ceremony 2003 - Part 3
Continuation of the annual CEU Graduation Ceremony held on Wednesday, June 18, 2003 in the Vigadó Hall in the center of Budapest. This part continues with the conferring of the degrees to the graduates from Political Science Department (presented by Prof. Nenad Dimitrijevic), Sociology Department of Warsaw (Head of the Department could not be present) and the Department of Environmental Sciences and Policy (presented by Prof. Ruben Mnatsakanian). After conferring the Master’s degrees, Stefan Messmann and the Head of the Departments award the PhD candidates who fulfilled all the academic requirements with their doctoral degree and the outstanding Master's graduates from each academic department and program with special prizes and acknowledgements. The commencement address is then delivered by the former president of Brazil, Fernando Henrique Cardoso, who spoke “In Defense of a Democratic Global Governance.”